2022
DOI: 10.1186/s12935-022-02604-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the chemokine receptor 3 pathway leads to a better response to immune checkpoint inhibitors in patients with metastatic urothelial carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) have made important breakthrough in anti-tumor therapy, however, no single biomarker can accurately predict their efficacy. Studies have found that tumor microenvironment is a key factor for determining the response to ICI therapy. Cytokine receptor 3 (C-X-C Motif Chemokine Receptor 3, CXCR3) pathway has been reported to play an important role in the migration, activation, and response of immune cells. We analyzed survival data, genomics, and clinical data from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…This is further supported by the elevated levels of IL-10, IL1-RA, CXCL9 and CXCL10 in cluster 1 with improved OS highlighting these markers as potential biomarkers of enhanced anti-tumor activity in ICI therapy. Specifically, these inflammatory chemokines bind to the CXCR3 receptor and specifically target activated T lymphocytes and natural killer (NK) cells (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the elevated levels of IL-10, IL1-RA, CXCL9 and CXCL10 in cluster 1 with improved OS highlighting these markers as potential biomarkers of enhanced anti-tumor activity in ICI therapy. Specifically, these inflammatory chemokines bind to the CXCR3 receptor and specifically target activated T lymphocytes and natural killer (NK) cells (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, there is a higher CXCL9/10-CXCR3-pathway-score protein expression in responder patients. Altogether, this suggests that a higher CXCR3-CXCL9/10 axis activation results in a better response to immunotherapy in this setting [ 140 ]. In a French cohort of 60 stage III/IV advanced NSCLC from whom a plasma soluble factors analysis was conducted before an immunotherapy injection, we showed that higher CXCL10 levels were correlated with a better response to first-line treatment, consisting of platinum-based doublet chemotherapy.…”
Section: Usefulness Of Chemokines Released During Icd As a Biomarkermentioning
confidence: 99%
“…For example, Zhou et al used the ssGSEA score of DDR and its subpathways, to investigate the effect of the DDR pathway activation status on the prognosis of patients with metastatic urothelial carcinoma [ 21 ]. Feng et al used ssGSEA to discover that a high activation status of the chemokine receptor 3 pathway presents as a potential prognostic predictor for patients treated with immune checkpoint inhibitors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%